Pharmacological Insights into Curcumin: From Traditional Remeadyto Modern Therapeutic Agents - Thorat Sakshi S,; Jadhav Diksha N., (Asian Journal of Pharmaceutical Research and Development, 2025)
Curcumin is the main active compound found in turmeric, which comes from the plant Curcuma longa.It has been used in Indian medicine and cooking for a long time because of its many health benefits. Modern research shows that curcumin has strong antioxidant, anti-inflammatory, antimicrobial, neuroprotective, and anticancer properties. These effects happen because curcumin affects various molecules and pathways in the body, such as NF-ÎºB, TLR4, and inflammatory chemicals like IL-6, TNF-Î±, and IL-1Î². Even though curcumin is promising for treatment, its use is limited by poor absorption in the body due to low solubility, quick metabolism, and fast removal. Recent developments in drug delivery systems, like nanoemulsions and nanoparticles, have improved its stability and uptake. Curcumin is considered safe in humans and animals, and it's being used in both traditional medicine and modern medical treatments. This summary covers curcumin’s structure, how it works in the body, its health effects, ways to improve its use, its safety, and its medical applications.